2009
DOI: 10.1007/s10862-009-9171-z
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Evaluation of the Thought Control Ability Questionnaire (TCAQ) and the Prediction of Cognitive Control

Abstract: Study 1 evaluated the psychometric properties of the English version of the Thought Control Ability Questionnaire (TCAQ; Luciano, Algarabel, Tomás, & Martínez, 2005), an index of perceived control over intrusive cognitions. Confirmatory factor analysis in a sample of 720 University students revealed a clear uni-dimensional structure (after removal of items 5, 7, 8, 14, and 25) with high internal consistency (α = .87, 95% CI = [.86, .88]) and test-retest reliability after a six month interval (r = .68). Correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 30 publications
1
37
0
2
Order By: Relevance
“…However, this difference did not moderate the effect of instructed thought suppression or HRV. The most likely explanation for this finding is that it is simply due to chance, as other studies that have employed the current study design with samples of undergraduate students have not observed these differences (Grisham & Williams, ; Williams et al, ).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…However, this difference did not moderate the effect of instructed thought suppression or HRV. The most likely explanation for this finding is that it is simply due to chance, as other studies that have employed the current study design with samples of undergraduate students have not observed these differences (Grisham & Williams, ; Williams et al, ).…”
Section: Resultsmentioning
confidence: 70%
“…Participants then completed a task in which they were asked to monitor the occurrence of a personally relevant intrusive thought. Variations of this thought suppression task have been successfully employed in a number of recent studies (Grisham & Williams, ; Williams et al, ). First, participants were instructed to type the name of a loved one into the computer.…”
Section: Methodsmentioning
confidence: 99%
“…TCAQ is a 25-item self-report questionnaire used to measure the ability of an individual to control unwanted and intrusive thoughts (Williams et al, 2010). TCAQ has a high test–retest reliability and good internal consistency (Luciano et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…325thought control ability (as measured by the TCAQ;Luciano, Algarabel, Tomás, & Martínez, 2005; greater scores on the TCAQ are negatively associated with both anxiety and depression as well as obsessive-compulsive disorder;Williams et al, 2010), and dissociative disorders (as measured by the Dissociative Experiences Scale, DES;…”
mentioning
confidence: 99%